International competition over artificial intelligence. Issue 3 (16th March 2022) - Unknown
Abstract : Artificial intelligence (AI) technology has become vastly more powerful and sophisticated in recent years. It remains fundamentally brittle and opaque, however, and this will limit its use in high-risk applications. If a race emerges between countries to develop and deploy cutting-edge AI, that competition will occur over both technological capabilities and over the more practical matter of whether these capabilities can be made to be trustworthy